Combination therapy of vaccinia virus infection with human anti-H3 and anti-B5 monoclonal antibodies in a small animal model - McCausland, Megan M. (2010)
Vaccinia virus possesses two immunologically distinct virion forms in vivo—mature virion (MV, IMV) and extracellular virion (EV, EEV). Here we show that combination therapy with two fully human mAbs against an immunodominant MV antigen, H3 (H3L), and an EV antigen, B5 (B5R), provides significantly better protection against vaccinia infection in a small animal model of progressive vaccinia (SCID mice infected with VACV(NYCBOH) vaccine strain) than a single human monoclonal or human vaccinia immune globulin (VIG), the currently licensed therapeutic for side effects of smallpox vaccination.